Historiography, Authoritarianism, and the Formation of Political Culture in Indonesia: Post-1965 Historiography and the Legacy of the New Order - Yusron Ihza; Linda Sunarti; Didik Pradjoko (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The 1965 political crisis marked a critical turning point in Indonesian history, shaping political culture and state–society relations. Although previous studies have examined political violence and regime consolidation, limited attention has been paid to how historiography normalized authoritarian values and political authority across generations. Objective: This study aims to analyze how historical narratives surrounding the 1965 crisis contributed to the formation and persistence of authoritarian political culture in Indonesia. Methods: This research employs a qualitative historical approach combined with historiographical analysis. Data were collected from historical archives, state narratives produced during the New Order period, historiographical literature, and scholarly works discussing political culture and authoritarian legacies in Indonesia. The data were analyzed using thematic discourse analysis to identify recurring political concepts embedded within official narratives. Results: The findings indicate that post-1965 historiography functioned not merely as a form of historical interpretation but also as an instrument of political legitimization. Specifically, state-sanctioned educational materials, such as the mandatory school curriculum portraying the PKI as a national threat, and the compulsory screening of Pengkhianatan G30S/PKI, reinforced hierarchical political norms. Narratives emphasizing stability, national unity, and anti-communism contributed to the construction of hierarchical political relations and the limitation of political pluralism. Furthermore, these political ideas continued to influence public trust, political participation, and perceptions of authority even after the democratic transition that followed the fall of the New Order regime in 1998. Conclusion: This study shows that historiography shapes political culture beyond regime change by sustaining authoritarian legacies through collective historical memory.